Rekonstruksi Pendidikan Islam Multikultural Indonesia Perspektif Filsafat Pendidikan Islam - Ismunadi, Ali; Khusni, Moh. Faishol (Tribakti: Jurnal Pemikiran Keislaman, 2021)
Efforts to explore various basic principles and ideals of Islamic education have become exciting studies in the discourse on Islamic philosophy. This study is even more interesting when juxtaposed with contemporary lessons such as multiculturalism and Islam Nusantara. Ironically, this discourse has stagnated in academic debate. In this context, the researcher uses a literature study approach by examining primary sources in the Islamic philosophical thought family. This research aims to see the philosophical basis with dimensions, principles, norms, and values ​​that live and use as human guidance. In this study, the researcher finds that from the perspective of Islamic philosophy, the basis of multiculturalism base on the Islamic doctrine of Rahmatallil'alamin. The common goal in the formation of humans is perfect humans as servants of Allah, social beings, and part of the universe. This basic principle is relevant to apply to humans in Indonesia who are diverse in culture, ethnicity, and religion.